Implementasi Hukum Ekonomi Syariah Dalam Penyelenggaraan Good Corporate Governance Bank Syariah - Trinita, Clara Happy (Media Hukum Indonesia (MHI), 2025)
The implementation of Good Corporate Governance (GCG) in Islamic banks has an important role in creating a transparent, accountable, and sharia-compliant banking system. This study aims to analyze the regulation and implementation of GCG in Islamic banking in Indonesia through normative legal research methods with a statutory and conceptual approach. Data sources include regulations such as Bank Indonesia Regulation No. 11/33/PBI/2009, Financial Services Authority Regulation No. 18/POJK.03/2014, and Law No. 21 of 2008 concerning Islamic Banking, which are analyzed qualitatively using the deductive method. The results of the study indicate that the regulations implemented have contributed to strengthening the governance of Islamic banks, but still face challenges such as low Islamic financial literacy in the community, competition with conventional banks, limited competent human resources, and the need for harmonization between Islamic law and national positive law. To overcome these challenges, it is necessary to improve Islamic financial education, strengthen more comprehensive regulations, and synergize between financial authorities, academics, and industry players in creating a stronger Islamic banking ecosystem. In conclusion, the effective implementation of GCG in Islamic banks does not only depend on regulations, but also requires support from various parties so that the Islamic banking system can develop more optimally and be trusted by the wider community.